(untitled) (Academicia Globe: Inderscience Research, 2023)
In developed countries, SIDS (also called crib death or cot death) accounts for 20 percent of deaths between the ages of one month and one year. SIDS is a categorization rather than an explanation, for the label is given when no reason for death can be found from the infant’s medical history or even after autopsy.